Determinants of sales tax compliance in small and medium enterprises in Jordan: a call for empirical research - Alshir’ah, Ahmad Farhan (IDOSI Publications, 2016)
Taxation is a major source of revenue for majority of countries.Efficient tax administration and strategies is vital to minimize loss of revenues, as such losses could lead to continuous budget deficits.Non-compliance of tax provision is a global phenomenon. The causes for tax non compliance raise significant cases for governments and tax agencies worldwide.This paper discusses the importance of sales tax in small and medium enterprise (SME) sector in Jordan and more importantly, signaling the severity of tax gap that should be addressed by Jordanian government. The paper urges tax authority and researchers, in particular,to carry out research on sales tax determinants in Jordan, by adapting the Fischer tax compliance model, which integrates both the economics deterrence and the social-psychology theories.Empirical study of this nature is highly recommended as the outcome are expected to provide significant input to the policy makers in streamlining and straitezing so as to minimize losses of revenues to the government.